2021
DOI: 10.1177/23337214211018924
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Mobile Health Technology use and Self-rated Quality of Life: A Cross-sectional Study on Older Adults with Cognitive Impairment

Abstract: Background: Quality of life (QoL) is affected even at early stages in older adults with cognitive impairment. The use of mobile health (mHealth) technology can offer support in daily life and improve the physical and mental health of older adults. However, a clarification of how mHealth technology can be used to support the QoL of older adults with cognitive impairment is needed. Objective: To investigate factors affecting mHealth technology use in relation to self-rated QoL among older adults with cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Despite the improvement in self-efficacy, Fanning et al ( 44 ) did not observe any meaningful improvement in the quality of life of the older adults despite the comprehensive mHealth app that was implemented. Conversely, Christiansen et al ( 45 ) observed improved quality of life following the implementation of a mHealth app for older adults with mild cognitive impairment noting that having moderately or high technical skills in using mHealth technology and using the internet via mHealth technology on a daily or weekly basis was associated with good to excellent QoL. Despite the mixed findings, these studies did not examine the sustained effects of the mHealth apps beyond the intervention duration which makes it rather difficult to draw stronger conclusions in relation to the current study.…”
Section: Related Workmentioning
confidence: 97%
“…Despite the improvement in self-efficacy, Fanning et al ( 44 ) did not observe any meaningful improvement in the quality of life of the older adults despite the comprehensive mHealth app that was implemented. Conversely, Christiansen et al ( 45 ) observed improved quality of life following the implementation of a mHealth app for older adults with mild cognitive impairment noting that having moderately or high technical skills in using mHealth technology and using the internet via mHealth technology on a daily or weekly basis was associated with good to excellent QoL. Despite the mixed findings, these studies did not examine the sustained effects of the mHealth apps beyond the intervention duration which makes it rather difficult to draw stronger conclusions in relation to the current study.…”
Section: Related Workmentioning
confidence: 97%
“…Some other neuropathological conditions can also be represented by cognitive impairment such as autism spectrum disorder (ASD) [ 165 , 166 , 167 ], and attention deficit hyperactive disorder (ADHD) [ 168 , 169 ]. The cases of cognitive impairments result in the lower quality of life among the suffering individuals, increase social and economic burden to the society in general and to the families of patients in particular [ 170 , 171 , 172 , 173 , 174 ]. Imbalanced levels of neurotransmitters such as glutamate, dopamine, acetylcholine, and GABA are linked with cognitive impairments [ 175 ].…”
Section: Allicin As a Neuroprotective Agent To Fight Against Neurological Diseasesmentioning
confidence: 99%